Congenital anterior urethrocutaneous fistula: a single-center retrospective study - Yang, Chao; Zhang, Chi; Cao, Yongsheng; Yu, Xin (Frontiers in Surgery, 2025)
BackgroundThis study aims to investigate the clinical characteristics and treatment strategies for congenital anterior urethrocutaneous fistula.MethodsWe retrospectively analyzed the clinical data of patients with congenital anterior urethrocutaneous fistula who underwent surgical treatment at Anhui Children's Hospital from December 2009 to February 2023. Data collected included patient demographics, preoperative fistula characteristics, surgical details, and postoperative outcomes. Postoperative follow-up was conducted regularly to evaluate clinical outcomes.ResultsThe average age of the eight patients was 31.38 ± 18.70 months. Fistula locations included three at the coronal sulcus, three at the penile midshaft, one at the penoscrotal junction, and one on the scrotum. The mean length of the fistulas was 0.66 ± 0.28 cm. Two patients presented with associated penile curvature and scrotal raphe splitting, while one had isolated penile curvature. Seven patients underwent primary repair: for cases with fistulas at the coronal sulcus (Cases 2 and 8), the Mathieu technique was utilized due to well-developed glans and sufficient ventral subcutaneous tissue; three patients (Cases 1, 3, and 5) with well-developed urethral plates underwent the Duplay technique; for two cases (Cases 4 and 7) with narrow urethral plates, the TIP and Onlay techniques were employed, respectively. In Case 6, due to severe penile curvature, a staged approach was necessary, involving transection of the urethral plate with initial Duckett procedure and proximal urethrostomy, followed by urethrostomy closure as a secondary procedure. The mean duration of the first-stage surgery for all 8 patients was 100.75 ± 27.88 min. The urinary catheters were removed 12–14 days postoperatively for all surgeries. During a follow-up period of 15–154 months, all patients exhibited normal urination with no evidence of urethral fistula, stricture, diverticulum, or recurrent penile curvature.ConclusionsThe surgical outcomes of congenital anterior urethrocutaneous fistula are generally favorable. For patients without penile curvature, with well-developed urethral plates and sufficient surrounding fascial tissue, the Mathieu or Duplay techniques are suitable for repair. The Onlay or TIP techniques may be preferred for those with narrow urethral plates. For cases with severe penile curvature, transection of the urethral plate with staged repair may be warranted.